(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
One of the most common mental health conditions in the world, depression severely reduces social functioning, productivity, and personal well-being. Over 300 million people are impacted globally, and by 2040, it is expected to overtake all other causes of disability. A thorough discussion of major depression, also known as major depressive disorder, is given here, along with an examination of its complex etiology, which includes genetic, neurochemical, and sociocultural factors. Its pathogenesis is primarily characterized by the dysregulation of the hypothalamic-pituitary-adrenal axis, glutamatergic signaling, and monoaminergic transmitters including dopamine, serotonin, and norepinephrine. Due to their delayed onset, adverse effects, and resistance to therapy, conventional antidepressant therapies such as selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, tricyclic antidepressants, and monoamine oxidase inhibitors remain first-line treatments. In addition, this review covers new approaches to treatment, including psychedelic-assisted therapy, brain stimulation techniques such as electroconvulsive therapy, transcranial magnetic stimulation, deep brain stimulation, and vagus nerve stimulation and rapid-acting pharmaceuticals such as ketamine and esketamine. The use of medicinal plants such as Withania somnifera, Curcuma longa, Hypericum perforatum, and others demonstrates promise due to their multi-targeted action, safety, and accessibility. These phytochemicals modulate neurotransmitter activity, reduce oxidative stress, and support neurotrophic factors. A holistic and personalized treatment approach, integrating pharmacotherapy, neurostimulation, and complementary herbal medicine, may optimize outcomes in depression management. Addressing stigma, increasing early diagnosis, and ensuring mental health-care accessibility remain imperative. Future research should focus on novel drug targets, patient-tailored therapies, and bridging the gap between traditional and modern practices.